Community structure and metabolic potentials of the traditional rice beer starter ‘emao’ - Diganta Narzary (Nature Portfolio, 2021)
Abstract The emao, a traditional beer starter used in the North–East regions of India produces a high quality of beer from rice substrates; however, its microbial community structure and functional metabolic modules remain unknown. To address this gap, we have used shot-gun whole-metagenome sequencing technology; accordingly, we have detected several enzymes that are known to catalyze saccharification, lignocellulose degradation, and biofuel production indicating the presence of metabolic functionome in the emao. The abundance of eukaryotic microorganisms, specifically the members of Mucoromycota and Ascomycota, dominated over the prokaryotes in the emao compared to previous metagenomic studies on such traditional starters where the relative abundance of prokaryotes occurred higher than the eukaryotes. The family Rhizopodaceae (64.5%) and its genus Rhizopus (64%) were the most dominant ones, followed by Phaffomycetaceae (11.14%) and its genus Wickerhamomyces (10.03%). The family Leuconostocaceae (6.09%) represented by two genera (Leuconostoc and Weissella) was dominant over the other bacteria, and it was the third-highest in overall relative abundance in the emao. The comprehensive microbial species diversity, community structure, and metabolic modules found in the emao are of practical value in the formulation of mixed-microbial cultures for biofuel production from plant-based feedstocks.